Nekrobiosis Lipoidica in a Pediatric Patient - Gözde Emel Gökçek; Özge Şeyda Saka; Emine Colgecen; Murat Borlu; Özlem Canöz (Galenos Publishing House, 2021)
Necrobiosis lipoidica is a rare chronic granulomatous disease that has historically been associated with diabetes mellitus, but recently it is thought to be secondary to microangiopathic changes. We report a necrobiosis lipoidica case of a five-year-old girl with diabetes since the age of two, because it is exceptionally unusual in pediatric diabetes. Necrobiosis lipoidica should be considered in pediatric patients with slowly expanded erythematous plaques and patches. This will help protect the patient from other important diabetic microangiopathic complications, such as nepropathy and retinopathy and also malignant progression, such as squamous cell carcinoma.